2021
DOI: 10.1007/s00248-021-01882-w
|View full text |Cite
|
Sign up to set email alerts
|

Bee Trypanosomatids: First Steps in the Analysis of the Genetic Variation and Population Structure of Lotmaria passim, Crithidia bombi and Crithidia mellificae

Abstract: Trypanosomatids are among the most prevalent parasites in bees but, despite the fact that their impact on the colonies can be quite important and that their infectivity may potentially depend on their genotypes, little is known about the population diversity of these pathogens. Here we cloned and sequenced three non-repetitive single copy loci (DNA topoisomerase II, glyceraldehyde-3-phosphate dehydrogenase and RNA polymerase II large subunit, RPB1) to produce new genetic data from Crithidia bombi, C. mellifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…In the present study L. passim, the most prevalent honeybee trypanosomatid, was identified in bumblebees. Similar observations were made by Bartolome et al [37] who confirmed the simultaneous presence of L. passim and C. mellificae in two B. terrestris individuals.…”
Section: Introductionsupporting
confidence: 90%
“…In the present study L. passim, the most prevalent honeybee trypanosomatid, was identified in bumblebees. Similar observations were made by Bartolome et al [37] who confirmed the simultaneous presence of L. passim and C. mellificae in two B. terrestris individuals.…”
Section: Introductionsupporting
confidence: 90%
“…It was detected in honey bee colonies throughout the year, at all seasons, and no differences were found between interior and forager bees, indicating it is a common organism in bee colonies. Together with the apparent absence of haplotype differentiation in L. passim, C. mellificae, or C. bombi between their hosts [38], these data suggest that insect trypanosomatids may infect a wider range of species than was previously thought.…”
Section: Discussionmentioning
confidence: 52%